2022
DOI: 10.3390/pharmaceutics14020417
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Mechanically Processed Stromal Vascular Fraction in a Chamber Vascularized by an Arteriovenous Shunt

Abstract: Mechanically processed stromal vascular fraction (mSVF) is a promising source for regenerative purposes. To study the in vivo fate of the mSVF, we herein used a vascularized tissue engineering chamber that insulates the target mSVF from the surrounding environment. In contrast to previous models, we propose an arteriovenous (AV) shunt between saphenous vessels in rats without a venous graft. Mechanical SVF was processed from the fat pads of male Sprague Dawley rats, mixed with a fibrin hydrogel and implanted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
2
0
1
Order By: Relevance
“…While the scaffold itself was designed for another research rationale, i.e., osteoarthritis and the design of a 3D structure by a custom bioreactor, our experiments neglected 3D characteristics as they are of secondary interest for wound healing purposes where the key goal is to generate a vascularized tissue layer. However, in accordance with O'Donnell's observations, our previous studies showed that mSVF has proadipogenic and importantly pro-angiogenic properties [27] that support mSVF as a suitable cell source. O'Donnell and colleagues used the same stock solution of GelMA (15 wt%), while photoactivation was only two minutes compared to five minutes in our approach, most likely due to smaller construct sizes and the more liquid texture of mSVF.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…While the scaffold itself was designed for another research rationale, i.e., osteoarthritis and the design of a 3D structure by a custom bioreactor, our experiments neglected 3D characteristics as they are of secondary interest for wound healing purposes where the key goal is to generate a vascularized tissue layer. However, in accordance with O'Donnell's observations, our previous studies showed that mSVF has proadipogenic and importantly pro-angiogenic properties [27] that support mSVF as a suitable cell source. O'Donnell and colleagues used the same stock solution of GelMA (15 wt%), while photoactivation was only two minutes compared to five minutes in our approach, most likely due to smaller construct sizes and the more liquid texture of mSVF.…”
Section: Discussionsupporting
confidence: 86%
“…Also, the authors used a composite hydrogel composed of GelMA and hyaluronan. We, by contrast, intentionally skipped additional components, as the mSVF itself is not a pure cell mixture but also includes significant amounts of extracellular matrix (ECM) molecules as demonstrated earlier [ 27 ]. O’Donnell et al investigated GelMA as a promising scaffold in an in vitro study reporting increased cell differentiation of ASCs into mature adipocytes when combined with the hydrogel [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luer lock) Nano Transfer PB-600.75 (ООО «ПАКТ-МедСервис», Россия) минимум 30 пассажами. Эмульсифицированный жир центрифугировали при 1 200 g в течение 5 мин., в результате чего образовавшийся верхний слой убирали, нижний слой использовали в качестве мСВФ [16].…”
Section: приготовление мсвфunclassified